Learning to Write News Texts in Grade VII of SMP Negeri 11 Pontianak City (A Case Study) - Fitriani Fitriani; Muhammad Lahir; Mericrise Antonia (Transpublika Publisher, 2025)
Writing skills are an essential component of language learning that enable students to express ideas and communicate effectively through written form. However, in many schools, students still experience difficulties in producing structured and coherent writing, particularly in composing news texts that require accuracy and factual presentation. This study aims to describe how the learning process of writing news texts takes place, the obstacles faced by students in the activity, and the steps taken by teachers to overcome student learning difficulties in grade VII of SMP Negeri 11 Pontianak City in the 2024/2025 academic year. The method used in this study is a descriptive case study with a qualitative approach. Data collection was carried out through observation, direct communication, indirect communication, and document analysis. The research instruments included observation guidelines, interview guidelines, questionnaire guidelines, and supporting documents. To maintain data validity, source triangulation techniques were used, while data analysis was carried out using an interactive model. The results of the study revealed that learning to write news texts in grade VII of SMP Negeri 11 Pontianak City was implemented through three stages: the pre-instructional stage, the instructional stage, and the evaluation and follow-up stage. Obstacles experienced by students came from both internal and external factors. Teachers’ efforts to overcome student learning difficulties were carried out by providing additional assignments, building effective communication with students, and utilizing devices in the learning process.